Literatur Review Efektivitas Pendidikan Kesehatan Melalui Media Untuk Meningkatkan Pengetahuan Ibu Hamil Terhadap Upaya Pencegahan Preeklampsia - Jannah, Muliatul; -, Resti Meilani; Meiranny, Arum (JIDAN Jurnal Ilmiah Bidan, 2024)
Background: Preeclampsia is a pregnancy-specific syndrome characterized by the onset of hypertension that occurs after 20 weeks of gestation, often accompanied by proteinuria and/or various organ failures including thrombocytopenia, hepatocellular necrosis, renal insufficiency, brain disorders, or pulmonary edema. One of the prevention efforts that can be done through health education activities. Health education is a collection of experiences that have a good influence on the habits, attitudes, and knowledge about the health of a person, community, and country. Health education can be done with several media to provide knowledge to pregnant women. Objective: to analyze more deeply the effectiveness of health education through media to increase the knowledge of pregnant women towards preeclampsia prevention efforts that are in accordance with previous studies by reviewing several studies. Methods: This review uses several national and international sources that have been published from databases (PubMed and Google Scholar) taken within the last 10 years from 2019-2023. The articles obtained in the search amounted to 10 journals with 6 national journals and 4 international journals. Results: the literature review shows that the provision of health education through the media is very influential in increasing the knowledge of pregnant women towards preeclampsia prevention efforts. These results are expected to provide interventions in the scope of midwifery and increase knowledge, especially for midwives and pregnant women to be able to make early prevention efforts in dealing with preeclampsia.